SENSE - Ultimate Low Light-Level Sensor Development. (February 2019) - Bonanna, G.; Haungs, A.; Henjes-Kunst, K.; Huber, T.; Link, K.; Nagai, A.; Mirzoyan, R.; Montaruli, T.; Romeo, G.; Strom, D.; Tajima, H.
Abstract: SENSE, a roadmap for the ideal low light-level sensor development is a project funded by the European Commission under Future and Emerging Technologies (FET) Open Coordination and Support Action (CSA). It aims at coordinating, monitoring, and evaluating the R&D efforts of research groups and industry in advancing low light-level (LLL) sensors and liaise with strategically important European initiatives and research groups and companies worldwide. The projects objectives are: (1) to conduct the development of a European R&D roadmap towards the ultimate LLL sensors, and to monitor and evaluate the progress of the development with respect to the roadmap, (2) to coordinate the R&D efforts of research groups and industry in advancing LLL sensors and liaise with strategically important European initiatives and research groups and companies worldwide, (3) to transfer knowledge by initiating information and training events and material, (4) to disseminate information by suitable outreach activities. The consortium has four partners: the Deutsches Elektronen Synchrotron (Coordinator), Germany; the Université de Genève, Switzerland; the Max-Planck Institute for Physics, Germany and Karlsruhe Institute of Technology, Germany. Several international experts for all areas of LLL development are involved in SENSE, some advise the project n the Experts Group and the others in the working group of the project which is regulated by a Cooperation Agreement.